Conditional Cash Transfers and Complementary Public Services: The Ecuadorian Case. - Espín, Jéssica (2021)
Selecting the right tools to combat poverty and inequality has become a major challenge for governments. Conditional Cash Transfer Programs have been widely promoted in Latin America and the Caribbean. However, these investigations leave aside elements that are part of the purposes of this type of program and that, when considered with the relevance that is required, can significantly contribute to a greater impact of this social protection instrument. Ecuador is part of the group of countries that promotes this policy and the objective of this study is to identify whether the Ecuadorian state provides sufficient guarantees to the program, which is considered the main tool in the fight against poverty; In this way, it is intended to outline the scope and limitations of this CCTP called Human Development Bond. The dimensions to be analyzed include the supply of public services and budget sustainability. The main conclusion of the investigation is that the State has difficulties in providing the guarantees, links and sufficient resources to achieve its objectives and, therefore, the application of said program does not have the expected impact.